THE USAGE OF TECHNOLOGIES IN TERRESTRIAL MEASUREMENTS FOR HAZARD MAPS - VELE Dan; ALEXE Mircea; STOIAN Ioan (Analele Universităţii din Oradea: Seria Geografie, 2015)
In the context of natural phenomena (earthquakes, floods, landslides etc.) bring economical and social prejudices year by year, watching on them and taking decisions becomes mandatory for reducing the material and human lives loss. Making hazard maps represents a tool used on wide global scale but also particularly in our country. This paper work has the purpose to reveal the interests of certain authors related to the usage of the new technologies of terrestrial measurements (GPS technologies, photogrammetry, cartography and of remote sensing) in order to make these hazard maps.